Importance of the Equatorial Undercurrent on the sea surface salinity in the eastern equatorial Atlantic in boreal spring. Issue 1 (25th January 2017) - Da‐Allada, C. Y.; Jouanno, J.; Gaillard, F.; Kolodziejczyk, N.; Maes, C.; Reul, N.; Bourlès, B.
Abstract: The physical processes implied in the sea surface salinity (SSS) increase in the equatorial Atlantic Cold Tongue (ACT) region during boreal spring and the lag observed between boreal spring SSS maximum and sea surface temperature (SST) summer minimum are examined using mixed‐layer salinity budgets computed from observations and model during the period 2010–2012. The boreal spring SSS maximum is mainly explained by an upward flux of high salinity originating from the core of the Equatorial Undercurrent (EUC) through vertical mixing and advection. The vertical mixing contribution to the mixed‐layer salt budget peaks in April–May. It is controlled primarily by (i) an increased zonal shear between the surface South Equatorial Current and the subsurface EUC and (ii) the presence of a strong salinity stratification at the mixed‐layer base from December to May. This haline stratification that is due to both high precipitations below the Inter Tropical Convergence Zone and zonal advection of low‐salinity water from the Gulf of Guinea explains largely the seasonal cycle of the vertical advection contribution to the mixed‐layer salt budget. In the ACT region, the SST reaches its maximum in March/April and minimum in July/August. This SST minimum appears 1 month after the maximum of SSS. The 1 month lag observed between the maximum of SSS in June and the minimum of SST in July is explained by the shallowing of the EUC salinity core in June, then the weakening/erosion of the EUC in June–July which dramatically reduces the lateral subsurface supply of high‐saline waters. Key Points: Large SSS increase during boreal spring in the equatorial Atlantic Cold Tongue (ACT), with 1 month lag between the maximum of SSS in June and the minimum SST in July Oceanic vertical processes and erosion of the Equatorial Undercurrent (EUC) salinity drive the boreal spring SSS maximum